‘Oh, honey, we’re all transgender’: the Journey towards Trans Subjectivity in US Fiction for Teens - Macleod, Mark (SOLETRAS, 2014)
The author of Geography Club (2003), Brent Hartinger, argues that LGBTI fiction in theUnited States has moved beyond its preoccupation with identity and coming out, and nowincludes characters who just happen to be gay (Hartinger 2009). He is defining his ownpractice as a writer accurately enough, but it’s not true to say that the coming out novel forteens is dead – or that it should be. Every young person’s experience of coming to terms withhis or her sexuality is unique, but before we assume that acknowledging LGBTI sexuality isno longer a problem, we need to remember that it can still be a matter of life and death in anincreasing number of communities. Namaste (2011) calls on academics to continue to makethe invisible lives of transgender people, in particular, visible by focusing on the alarmingfacts of their homelessness, their suffering of poor health and violent crime, and the tragic rateof transgender suicide. It is too comfortable for theorists such as Butler (1990) and Garber(1991) to focus on LGBTI as merely contesting intellectual constructions of gender. ForNamaste the function of discourse about diversity is to achieve social justice.